Metode Dongeng dalam Meningkatkan Perkembangan Kecerdasan Moral Anak Usia Prasekolah - Ahyani, Latifah Nur (Universitas Muria Kudus, 2010)
The research aims to know the storytelling method in increasing the development of moral intelligence of preschool children. Subject of the research is the five year students of kindergarten. The research is designed using model of The Untreated Control Group Design with Pretest and Posttest. This design uses two groups examined which consist of an experiment group and a control group. The measurement is conducted twice using moral intelligence measurement instrument, namely before it is given treatment (pre-test) and after it has been given treatment (post-test). The result of analysis using covariance analysis (anacova) shows that there is difference of moral intelligence achievement level of the preschool children between those who received moral value guidance using storytelling method and those who do not receive it. The result of analysis also shows that there is difference of moral intelligence achievement level before they receive moral value guidance through storytelling method and after the have received it. The importance of storytelling method toward the moral intelligence of preschool children is 34 %.